ChemInform Abstract: Non‐Precious‐Metal Catalytic Systems Involving Iron or Cobalt Carboxylates and Alkyl Isocyanides for Hydrosilylation of Alkenes with Hydrosiloxanes. Issue 33 (July 2016) - Noda, Daisuke; Tahara, Atsushi; Sunada, Yusuke; Nagashima, Hideo
Abstract: The catalyst systems are expected to be applicable to industrial processes for modification of silicon fluids and generation of silicon gels.